PENGARUH MOBILITAS MODAL TERHADAP PERTUMBUHAN EKONOMI DI SULAWESI SELATAN - Muarif Leo; Janna Meilani Ode (Unib Press Universitas Bengkulu, 2021)
The purpose of this research is 1)to examine and explain the effect of working capital, investments and consumption simultaneously positive and significant impact on economic growth in the Southeast. 2) to examine and explain the effect of working capital on economic growth. 3) To examine and explain the effect of the investment on economic growth 4) To examine and explain the effect of consumption to economic growth. The method used is quantitative research and using secondary data. Data analysis technique using multiple regeresi with the help of a software program Eviews 9.0. The results showed that 1) Consumption partially significant and positive impact on economic growth. 2) The investment is partially significant and positive impact on economic growth 3) Working capital is partially not significant and positive impact on economic growth. 4) Consumption, investment and working capital simultaneously significant and positive impact on economic growth.